Determinants associated with high-risk fertility behaviours among reproductive aged women in Bangladesh: a cross-sectional study - Md. Hasan Howlader; Harun Or Roshid; Satyajit Kundu; Henry Ratul Halder; Sanjoy Kumar Chanda; Md. Ashfikur Rahman (BMC, 2022)
Plain Language Summary High rates of maternal high-risk fertility behaviour (HRFB) have a variety of unfavourable repercussions for both the mother and the child. However, because there have been few studies on this topic to date, we set out to identify the determinants that enhance the risk of HRFB in Bangladeshi women between the ages of 15 and 49. Using latest demographic and health survey (BDHS) data we have found that 67.7% of women had HRFB, with 45.6% having a single high-risk factor and 22.1% having multiple high-risk factors. This high prevalence rate demonstrates that HRFB are all too common in Bangladesh, potentially endangering the health of the country's women. We found that women practicing Islam as core religion, age above 35 years, having normal childbirth, having above 3 children, having unwanted pregnancies and not using birth control methods were at increased risk of having HRFB. As a result of the study's findings, interventions are urgently needed to prevent high-risk fertility behaviour among Bangladeshi women aged 15 to 49 years.